Behaviour of adult sea trout Salmo trutta that survive or die at sea. (31st October 2019) - Kristensen, Martin Lykke; Righton, David; Villar-Guerra, Diego del; Baktoft, Henrik; Aarestrup, Kim
Abstract: We tagged 125 sea trout kelts (460–925 mm) in seven Danish rivers with positively buoyant DSTs. Fifty-three (42%) tags were recovered, enabling a comparison of behaviour in kelts that survived the marine period and kelts that did not. Data revealed an estimated mean survival time at sea of 14.3 days (range 1–65 days) for fish that died at sea. Fish that did not survive had lower weight/length ratios when tagged than survivors (P = 0.005) but exhibited a similar diel diving pattern while at sea. Both surviving and non-surviving fish gradually increased diving activity and the daily visited maximum depths after sea entry, but some performed fewer dives and resided in shallower depths than others. This difference was pronounced when comparing surviving fish (most active divers) with fish caught by anglers (least active divers). The results show that the first weeks at sea are critical for kelt survival and that physical status of kelts may affect behaviour and probability of survival. The preference for shallower waters and less diving activity in some individuals indicate that coastally based fisheries and recreational angling may select against specific behavioural phenotypes which should be investigated more intensively. Graphical abstract: Image 1 Highlights: Sea trout ( Salmo trutta) kelts were studied with a novel type of data storage tag. Mortality was high in the first three weeks after sea entry. Non-surviving fish had lower weight/length ratios when tagged than surviving fish. Surviving fish performed more frequent foraging dives than non-surviving fish. Angling from the coast could select against specific phenotypes in sea trout.